2021
DOI: 10.1002/2211-5463.13160
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of ZHX2 predicts poor prognosis and is correlated with immune infiltration in gastric cancer

Abstract: Running heading: ZHX2 predicts poor prognosis in gastric cancer. Abbreviations ZHX2 Zinc-finger and homeoboxes2 GC gastric cancer TIMER Tumor Immune Estimation Resourceti IHC immunohistochemical GSEA Gene set enrichment analysis TCGA The Cancer Genome Atlas qRT-PCR Real-time quantitative PCR CHOL Cholangiocarcinoma ESCA Esophageal carcinoma HNSC Head and Neck squamous cell carcinoma KIRC Kidney renal clear cell carcinoma KIRP Kidney renal papillary cell carcinoma LIHC Liver hepatocellular carcinoma SKCM-metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Consistent with findings in HCC, low ZHX2 expression correlates with poor prognosis of thyroid cancer (7), multiple myeloma (8)(9)(10), and chronic lymphocytic leukemia (11,12). On the contrary, ZHX2 promotes the development of ccRCC (13)(14)(15), TNBC (16), and gastric cancer (17,18). Beyond regulating cancer development, the latest reports have shown that ZHX2 involves in several other physiological or pathological processes, including cell differentiation and development (19)(20)(21), lipid metabolism (22)(23)(24), and viral replication (25,26).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Consistent with findings in HCC, low ZHX2 expression correlates with poor prognosis of thyroid cancer (7), multiple myeloma (8)(9)(10), and chronic lymphocytic leukemia (11,12). On the contrary, ZHX2 promotes the development of ccRCC (13)(14)(15), TNBC (16), and gastric cancer (17,18). Beyond regulating cancer development, the latest reports have shown that ZHX2 involves in several other physiological or pathological processes, including cell differentiation and development (19)(20)(21), lipid metabolism (22)(23)(24), and viral replication (25,26).…”
Section: Introductionsupporting
confidence: 63%
“…In addition, Zhu et al reported that ZHX2 promotes cell growth and migration through activating MEK/ ERK pathway and mediates Sunitinib resistance by regulating the autophagy in ccRCC (14). A similar phenomenon is found in studies of multiple osteosarcoma and gastric cancer (17,18), where high expression of ZHX2 shows a significant correlation with poor survival. Further, a recent study clarified that ZHX2 functions as a cofactor of the HIF1a to promote HIF1a oncogenic signaling in TNBC (16).…”
Section: Oncogenic Role Of Zhx2 In Ccrcc Tnbc and Other Tumorsmentioning
confidence: 53%
“…On the other hand, from tissue microarray and clinicopathological analyses, ZHX2 protein expression in metastatic HCC was twice as high as in the primary lesions, indicating that ZHX2 expression is associated with metastasis in HCC ( 16 ). Recently, our research and others have established the oncogenic role of ZHX2 in various cancers, including ccRCC, breast cancer, multiple myeloma, and gastric cancer ( 4 , 17 21 ). More interestingly, ZHX2 is localized on the 8q24 locus, where Myc is localized, and this locus has been reported to be amplified in many cancers, including breast cancer ( 22 ).…”
mentioning
confidence: 87%
“…The databases UALCAN (http://ualcan.path.uab.edu/) [18] and the Human Protein Atlas (https://www.proteinatlas.org/) [19] were searched for analysis of the HAUS5 mRNA levels in the dataset TCGA and HAUS5 protein levels, respectively. The Kaplan-Meier Plotter (https://kmplot.com/analysis/) [20] was employed to examine the associations between HAUS5 levels and patient survival rates. The database LinkedOmics (http://www.linkedomics.org/login.php) [21] was utilized to conduct pathway analysis and functional annotation of genes, whereas the two expression groups were subjected to Gene set enrichment analysis (GSEA) [22] concerning their differences in biological and functional pathways.…”
Section: Bioinformatic Analysismentioning
confidence: 99%